Photoconductive Detector Based on Graphene Doping with Silver Nanoparticles - Mohammed, Aya H.; Naje, Asama N.; Ibrahim, Rawa k. (Iraqi Journal of Science, 2022)
Graphene (Gr) decorated with silver nanoparticles (Ag NPs) were used to fabricate a wideband range photodetector. Silicon (Si) and porous silicon (PS) were used as a substrate to deposit Gr /Ag NPs by drop-casting technique. Silver nanoparticles (Ag NPs) were prepared using the chemical method. As well as the dispersion of silver NPs is achieved by a simple chemistry process on the surface of Gr. The optical, structure and electrical characteristics of AgNPs and Gr decorated with Ag NPs were characterized by ultraviolet-visible spectroscopy (UV-Vis), x-ray diffraction (XRD). The X-ray diffraction (XRD) spectrum of Ag NPs exhibited 2θ values (38.1o, 44.3 o, 64.5 o and 77.7 o) corresponding to the silver nanocrystal, while the XRD pattern of Gr-Ag NPs shows two distinct diffraction peaks at 2 θ = 26.2°and 54.7 which correspond to the (002), and (110). The absorption spectrum of Gr-AgNPs extended from UV to near IR region, surface plasmon resonance (SPR) absorption peak position for the AgNPs at ( 320-480) nm. The I-V characteristics for the photoconductive detector on Si were measured with three sources: UV, visible, and IR. The photocurrent increased under the illumination of UV light (10W, 365nm), a Tungsten lamp (250W, 500-800nm), and a laser diode (300mW, 808nm). The I-V characteristics for the photoconductive detector on PS were measured with three sources: UV, Visible, and IR. Furthermore, we coated polyamide-nylon polymer on Gr/Ag NPs samples deposited on a Si and PS layer by the drop-casting method the results show that the photocurrent increased for all samples.